Food safety public opinion analysis technology extraction method - WANG WEIYA; LIANG QIJUN; LIN DAN; XIE FENG; TAO GUANGCAN (2022)
The invention provides a food safety public opinion analysis technology extraction method, food safety content screening comprises a keyword matching method, an unsupervised clustering classification method and semantic sentiment analysis, and the semantic sentiment analysis comprises bert pre-training model and oftmax classification and information extraction. Information extraction comprises prompt tuning and KEP subject viewpoint extraction, food safety public opinion analysis plays an important auxiliary role in food safety research, along with development of artificial intelligence, combination of public opinion analysis and a natural language processing technology is tighter, and in public opinion analysis, the process is about news collection and content screening, and public opinion analysis is more reasonable. The method comprises the following steps: performing sentiment analysis on news related to food safety, completing primary screening of public opinion analysis, and performing event analysis an